Differential roles of Lck and Itk in T cell response to antigen recognition revealed by calcium imaging and electron microscopy. - Donnadieu, E; Lang, V; Bismuth, G; Ellmeier, W; Acuto, O; Michel, F; Trautmann, A (2001)
Ag recognition triggered at the interface between a T cell and an APC is conditioned by cell-cell adhesion and cytoskeletal remodeling. The role played in these phenomena by Lck and Itk, two protein tyrosine kinases essential for T cell signaling, was examined. Early T cell responses (membrane ruffling, Ca(2+) response, APC-T cell adhesion) were monitored in T cells overexpressing kinase-defective (KD) Lck and Itk mutants by combining fluorescence imaging and electron microscopy. Neither Lck nor Itk appears to be involved in the Ag-independent formation of a small and labile contact interface between T cells and APCS: By contrast, the Ag-induced Ca(2+) response in a cell population is similarly blunted in both KD transfectants. However, the underlying mechanisms are strikingly different for the two kinases. The major effect of Lck-KD is to reduce the probability of giving rise to quasi-normal Ca(2+) responses, whereas overexpression of Itk-KD results in a tuning down of all single-cell Ca(2+) responses. In addition, Lck, but not Itk, is required for the formation of a stable T/APC conjugate and for T cell polarization after Ag stimulation. Overall, our results lead to a clear distinction between Lck and ITK: Lck plays an ignition role, controlling all the downstream events tested here, whereas Itk amplifies the Ca(2+) response, but is dispensable for APC-induced adhesive and morphological responses.